The Effect of Acute Body Unloading on Somatosensory Performance, Motor Activation, and Visuomotor Tasks - Marchant, Ashleigh; Ball, Nick; Witchalls, Jeremy; Waddington, Gordon; Mulavara, Ajitkumar P.; Bloomberg, Jacob J. (Frontiers in Physiology, 2020)
Evaluating countermeasures designed to reduce the impact of microgravity exposure on astronaut performance requires the development of effective methods of assessing changes to sensorimotor function in 1g analog systems. In this study, somatosensation at the ankle and fingers, lower leg muscle activity and visuomotor control were assessed using a full body loading and acute unloading model to simulate microgravity. It was hypothesized that the function of the hands and eyes are not constrained to ‘weight bearing’ postures for optimal function and would not differ between the loaded and acute unloaded conditions, whereas lower leg muscle activity and ankle somatosensation would be reduced in the acute unloaded condition. Somatosensation was recorded using the Active Movement Extent Discrimination Apparatus (AMEDA) protocol where participants were required to make an absolute judgement of joint position sense. A score closer to 1.0 demonstrates higher accuracy. Lower leg muscle activity was recorded using electromyography of major lower leg musculature to observe peak muscle activity and duration of contraction. The King Devick infrared eye tracking test was used to asses visuomotor control by monitoring saccade velocity and fixation time. In acute unloading, it was found that ankle somatosensation had decreased accuracy (loaded 0.68, unloaded 0.66, p=0.045) while finger somatosensation improved (loaded 0.77, unloaded 0.79, p=0.006). When acutely unloaded, peak lower leg muscle activation reduced (>27%) and total contraction time increased (2.02 x longer) compared to loading. Visuomotor assessment results did not vary between the loaded and acute unloaded postures, however the underlying techniques used by the participant to complete the task (saccade velocity and fixations time) did increase in acute unloaded conditions. Significance: This research provides an insight to how to the human body responds immediately to acute changes of gravitational load direction. It provides insight to the acute affects’ astronauts may encounter when in microgravity.